(untitled) (Journal of the College of Basic Education, 2022)
The current research aimed to identify the effect of the Venn scheme strategy in developing coordination thinking among female students of the Institute of Fine Arts in the history of contemporary art, for female students of the fifth stage / Department of Fine Arts / Institute of Fine Arts for Girls / for the academic year (2021-2022). The design of the two groups (experimental control) and the two pre and posttests to achieve the goal of the research. The research sample was chosen from the female students of the fifth stage / Department of Fine Arts / for the morning study for the academic year (2021-2022), where the sample was randomly distributed into two groups, the first is an experimental group consisting of (20) female students studied using the Vinvenn scheme strategy, and the second is a control group consisting of (20) female students I studied in the traditional way. The researcher prepared a scale of coordination thinking consisting of (28) items with a five scale (1-5). The study found the effectiveness of using the venn scheme strategy in raising the level of achievement of female students of the Department of Fine Arts in the subject of contemporary art history.